Intra-arterial Foreign Body following Radial Artery Cannulation Requiring Microsurgical Removal: Case Report and Review of the Literature - Feinstein, Shawn D.; Draeger, Reid W. (Journal of Hand and Microsurgery, 2018)
We report the case of a pediatric patient who underwent intra-arterial exploration and removal of foreign body after an arterial catheter cannula inadvertently fractured during removal and a fragment remained within the radial artery. The fragment was visualized using fluoroscopy intraoperatively and was successfully removed from the common digital artery to the index finger where it had migrated. We present the case as a rare complication of an exceedingly common procedure with a timely response to avoid further complication.
Keywords: arterial line; complication; radial artery cannulation; microvascular repair